Elevated CO2 and ammonium nitrogen promoted the plasticity of two maple in great lakes region by adjusting photosynthetic adaptation - Wang, Lei; Dang, Qing-Lai (Frontiers in Plant Science, 2024)
Climate change-related CO2 increases and different forms of nitrogen deposition are thought to affect the performance of plants, but their interactions have been poorly studied. This study investigated the responses of photosynthesis and growth in two invasive maple species, amur maple (Acer ginnala Maxim.) and boxelder maple (Acer negundo L.), to elevated CO2 (400 µmol mol -1 (aCO2) vs. 800 µmol mol -1 (eCO2) and different forms of nitrogen fertilization (100% nitrate, 100% ammonium, and a equal mix of the two) with pot experiment under controlled conditions. The results showed that eCO2 significantly promoted photosynthesis, biomass, and stomatal conductance in both species. The biochemical limitation of photosynthesis was switched to RuBP regeneration (related to Jmax) under eCO2 from the Rubisco carboxylation limitation (related to Vcmax) under aCO2. Both species maximized carbon gain by lower specific leaf area and higher N concentration than control treatment, indicating robust morphological plasticity. Ammonium was not conducive to growth under aCO2, but it significantly promoted biomass and photosynthesis under eCO2. When nitrate was the sole nitrogen source, eCO2 significantly reduced N assimilation and growth. The total leaf N per tree was significantly higher in boxelder maple than in amur maple, while the carbon and nitrogen ratio was significantly lower in boxelder maple than in amur maple, suggesting that boxelder maple leaf liter may be more favorable for faster nutrient cycling.The results suggest that increases in ammonium under future elevated CO2 will enhance the plasticity and adaptation of the two maple species.